Youths, hip hop and Latin American cinema - Montoya, Wilfredo (2022)
This article provides evidence on the growing interest of Latin American cinema in hip hop. The cinematographic narration of these films portrays the lives of young people from popular classes who face situations marked by violence and deep social inequalities, through the practice of rap, break dance, graffiti and DJing, components of this culture. The article provides a recount of films and documentaries, made in eight Latin American countries, in the last decade. Analyzes above all three films released in 2021: This is how I grew up, by the mexican filmmaker Jos Macías; Cato, by argentine director Peta Rivero y Hornos; and The city of beasts, by colombian movie maker Henry Rincón. He argues that these provide a realistic and critical aesthetic reflection and confluent with de descolonial perspective of their respective societies, as well as a reading of a priority social sector such as popular youth, useful for understanding their current characteristics and prospects.